REŃLERDEGI “JAQSÍLÍQ” HÁM “JAMANLÍQ” SIMVOLLÍ KONNOTATIV MÁNILER - Bekbosinova, G.M. (SCIENCE and SOCIETY, 2025)
The article provides comments on the participation of yellow, red, green, blue, gray colors in the Karakalpak language in the composition of connotative semantic units that have both positive and negative connotation, which serve to ensure the effectiveness of speech.